Ne Bis in Idem Judgement in Criminal Cases of Money Laundering with a Predicate Crime of Corruption - Ahmadi, Ahmadi; Irawan, Benny; Herli, Dadang (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
Judicial application of ne bis in idem in Indonesian courts, where money laundering charges are dismissed after a corruption conviction, creates a serious legal problem. This study argues that, despite some judicial opinions, these are distinct crimes and not a single offense. Using a normative juridical approach and analyzing key court decisions (Jambi District Court Decision No. 282/PID.SUS/2015/PN.Jmb and Supreme Court Decision No. 321K/PID.SUS/2016), this research demonstrates that this practice undermines legal certainty and justice, allowing criminals to evade prosecution for a separate offense. The findings reveal the urgent need for a clear legal distinction between these two crimes and propose that appeals are the proper legal remedy to challenge such decisions, thereby strengthening law enforcement and asset recovery efforts.